2013
DOI: 10.1158/1078-0432.ccr-13-0295
|View full text |Cite
|
Sign up to set email alerts
|

Relapsed Classic E-Cadherin (CDH1)–Mutated Invasive Lobular Breast Cancer Shows a High Frequency ofHER2(ERBB2) Gene Mutations

Abstract: Purpose: We queried whether comprehensive genomic profiling using a next-generation sequencingbased assay could identify novel and unanticipated targets of therapy for patients with relapsed invasive lobular carcinoma (ILC).Experimental Design: DNA sequencing (Illumina HiSeq 2000) was conducted for 3,320 exons of 182 cancer-related genes and 37 introns of 14 genes frequently rearranged in cancer on indexed, adaptor-ligated, hybridization-captured libraries using DNA isolated from formalin-fixed paraffin-embedd… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
85
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 124 publications
(96 citation statements)
references
References 43 publications
9
85
0
2
Order By: Relevance
“…In the Bladder Urothelial Carcinoma TCGA dataset, although point mutations in ERBB2 are not described, amplification of ERBB2 was listed in 6% (9/150) of cases (The cBio Cancer Genomics Portal, April 2013). An enrichment of ERBB2 mutation within a common cancer subtype has also been recently described in a series of CDH1-mutated invasive lobular carcinomas of the breast with a frequency of 23% compared with a frequency of 2% in all breast cancers (19). Separate studies have reported ERBB2 amplification predominantly based on FISH analysis in 8% to 9% of primary urothelial carcinomas, and at a higher frequency in lymph node metastases (20).…”
Section: Discussionmentioning
confidence: 73%
“…In the Bladder Urothelial Carcinoma TCGA dataset, although point mutations in ERBB2 are not described, amplification of ERBB2 was listed in 6% (9/150) of cases (The cBio Cancer Genomics Portal, April 2013). An enrichment of ERBB2 mutation within a common cancer subtype has also been recently described in a series of CDH1-mutated invasive lobular carcinomas of the breast with a frequency of 23% compared with a frequency of 2% in all breast cancers (19). Separate studies have reported ERBB2 amplification predominantly based on FISH analysis in 8% to 9% of primary urothelial carcinomas, and at a higher frequency in lymph node metastases (20).…”
Section: Discussionmentioning
confidence: 73%
“…In contrast to the low rate of HER2 mutations (2%) observed in invasive ductal carcinomas, ILCs have a relatively high rate of HER2 mutations (23%) among those patients with relapsed disease, validated as ILC with identification of a CDH1 mutation. 17 Although this HER2 mutation rate in relapsed ILC is high, 17 HER2 mutations in primary invasive lobular carcinomas, although significant, are lower (approximately 9%). 14 Our study is consistent with these latter observations, finding that five (three classic and two pleomorphic lobular carcinomas, approximately 26% of the HER2 mutations) harbored kinase domain mutations.…”
Section: Co-occurrence Of Her2 Gene Amplification and Mutationmentioning
confidence: 96%
“…The test has been validated to detect base substitutions at ≥10% mutant allele frequency with ≥99% sensitivity and indels at ≥20% mutant allele frequency with ≥95% sensitivity, with a false discovery rate of <1%. 16,17 CRGAs were defined broadly as those with a targeted FDA-approved anticancer drug available or those with a targeted drug in registered phase 2 or phase 3 clinical trials. The success of CGP was categorized as either yielding a full, unqualified report (full analysis); a qualified report with guideline driven performance caveats (qualified report); the inability to sequence the tumor secondary to insufficient DNA (tissue insufficient for analysis); or the inability to sequence the tumor secondary to test failure (testing failure).…”
Section: Methodsmentioning
confidence: 99%
“…At least 50 ng of DNA per specimen was isolated and sequenced to high, uniform coverage (mean 734X) on the Illumina HiSeq2500 instrument, as previously described 16,17. Genomic alterations (base substitutions, short insertions and deletions, focal gene amplifications, homozygous deletions…”
mentioning
confidence: 99%